Topics in modal analysis II, volume 6 : proceedings of the 30th IMAC, a conference on structural dynamics, 2012 - De Clerck, J.; Niezrecki, C.; Blough, J.R; Allemang, R. (Conference Proceedings of the Society for Experimental Mechanics Series, 2012)
Topics in Modal Analysis II, Volume 6:  Proceedings of the 30th IMAC, A Conference and Exposition on Structural Dynamics, 2012, is the sixth volume of six from the Conference and brings together 65 contributions to this important area of research and engineering.  The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Aerospace Acoustics Energy Harvesting Shock and Vibration Finite Element Structural Health Monitoring Biodynamics Experimental Techniques Damage Detection Rotating Machinery Sports Equipment Dynamics Aircraft/Aerospace